3D-printed add-on allows using commercially available rotating disc electrodes in tilted position - Katharina Röhring; Falk Harnisch (Electrochemistry Communications)
Knowledge on reaction kinetics is essential for further understanding electrochemical reactions and the development of electrochemical processes. Different tools are available to study reaction kinetics of redox electrodes. One that is widely used is the rotating disk electrode (RDE). However, RDE has limitations when it comes to more complex electrochemical reactions, especially those involving gas evolution. Due to the facing downwards of the planar electrode surface evolving gas bubbles cannot escape by buoyance leading to temporarily and stochastically insultation. This limits using the RDE to low overpotentials or high rotation rates for these kind of reactions in order to prevent blockage of the electrode surface with gas bubbles. To overcome these limitations, we present a modification for commercially available RDE that is based on rapid prototyping using 3D-printing. This allows the RDE setup to be easily operated in a tilted position allowing the gas bubbles to escape from the electrode surface by buoyance. We validate the tilted RDE setup using the example of the well-studied redox pair ferro-/ferricyanide. This is achieved by calculating the diffusion coefficient for both redox species in straight and tilted position based on the Levich-equation. We show that the presented setup can be further used for more complex reactions.